2017
DOI: 10.17584/rcch.2017v11i2.6666
|View full text |Cite
|
Sign up to set email alerts
|

Uso de LEDs na multiplicação <i>in vitro</i> de três cultivares de bananeira

Abstract: Aspecto visual da sala de crescimento com os diferentes tipos de luz (LEDs, azuis, vermelhos, verdes e lâmpadas fluorescentes).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…However, in in vitro propagation of Alpinia cultivars, exposure to white LED for Red Ginger cultivar provided a higher number of sprouts (Pinheiro et al, 2019). This variation in the formation of sprouts between species and cultivars was also reported in the in vitro banana crop, where Rocha et al (2017) evaluated the use of fluorescent lights and LEDs and demonstrated that the use of LED helps sprout development with variations between cultivars.…”
Section: Resultsmentioning
confidence: 68%
“…However, in in vitro propagation of Alpinia cultivars, exposure to white LED for Red Ginger cultivar provided a higher number of sprouts (Pinheiro et al, 2019). This variation in the formation of sprouts between species and cultivars was also reported in the in vitro banana crop, where Rocha et al (2017) evaluated the use of fluorescent lights and LEDs and demonstrated that the use of LED helps sprout development with variations between cultivars.…”
Section: Resultsmentioning
confidence: 68%
“…For cultivar, regardless of the light source, Red Ginger was superior to Pink Ginger (Figure 1A). Rocha et al (2017), working with three banana cultivars, observed that the "Grande Naine" presented 2.6 shoots, with differences of almost a shoot when compared to the other cultivars. The same authors also reinforce that the LEDs can exert positive effects in the increase of the number of shoots, which can vary between the cultivars of the same species.…”
Section: Resultsmentioning
confidence: 99%
“…Os diodos emissores de luz (LEDs) são considerados uma opção bastante promissora, por apresentarem características importantes em relação às lâmpadas fluorescentes, que são convencionalmente usadas em laboratórios de micropropagação. Os LEDs possuem alta eficiência na geração de luz com baixa emissão de calor, podem ter sua intensidade e composição espectral controladas e, principalmente, são mais econômicos (Lazzarini et al, 2017;Rocha et al, 2017). Além disso, estudos mostraram que o uso de LEDs incrementa a taxa de multiplicação dos explantes e é capaz de proporcionar maior comprimento e número de brotações, devido à melhoria na qualidade de luz (Rocha et al, 2017).…”
unclassified